Influence of foliar micronutrients fertilization on nutritional status of apple trees - Gabriela Kurešová; Ladislav Menšík; Jan Haberle; Pavel Svoboda; Ivana Raimanová (Plant, Soil and Environment, 2019)
The effect of leaf-applied fertilizers on nutritional status and yields of apple cv. Rubinola grown on two soil types (Luvisol, Cambisol) differing in yield levels was studied in a three-year experiment at the orchard in Vanovice, Czech Republic. Two fertilizers, A (containing N, Mg, Ca, B and Zn) and B (N, B, Zn, Mn and Fe) were applied after blooming, leaves and fruit were analyzed. Zn and B concentrations increased significantly in leaves and fruit in both soils after the application of solution A compared to the control. Foliar fertilizer B increased the concentration of Zn and Mn significantly both in leaves and fruit compared to the control. The content of Mn in dry leaf matter increased almost 4 times (from the control level about 30 mg/kg), of B up to 1.5 times (from 28 mg/kg) and the content of Zn even more than 10 times (from 15 mg/kg). The application of foliar fertilizers was more efficient in the Cambisol orchard section with worse soil conditions; however, the enhanced nutritional status did not significantly increase fruit yields in either of the experimental soil types.